Menelusuri Perkembangan, Kondisi Terkini, dan Prospek Masa Depan Pengujian DNA dalam Aplikasi Forensik Manusia dan Non-Manusia: Tinjauan Naratif - Siboro, Dewi Pratiwi Purba; Zahra, Aliya Azkia; Kasasiah, Ahsanal; Malau, Jekmal; Aprillia, Cantika; Ainaputri, Aliza Salsabila; Nugraha, Afif Tri; Aprianti, Endeh (Journal of Pharmaceutical and Sciences, 2026)
DNA typing has become a cornerstone of modern forensic science, profoundly influencing criminal investigations, forensic human identification, and non-human forensic applications. Since its introduction in the mid-1980s, forensic DNA analysis has evolved from restriction fragment length polymorphism-based methods to polymerase chain reaction-based short tandem repeat profiling, and more recently to sequence-based approaches enabled by massively parallel sequencing, resulting in substantial improvements in analytical sensitivity, robustness, and discriminatory power. This narrative review aims to trace the historical development, examine the current state, and explore future directions of DNA typing in both human and non-human forensic contexts, with particular emphasis on empirical case studies from Asia. A narrative review methodology was employed through a comprehensive analysis of peer-reviewed literature published between 2015 and 2026, sourced from major scientific databases including Google Scholar, PubMed, and ScienceDirect, with studies selected based on forensic relevance, methodological rigor, and regional significance. The review highlights the extensive application of DNA typing in routine criminal casework, disaster victim identification, missing persons investigations, wildlife forensic genetics, food fraud detection, and biosecurity, and documents emerging technologies such as portable DNA systems and CRISPR-based detection. Despite these advances, significant challenges remain related to data interpretation, validation requirements, contamination control, ethical and legal governance, and uneven forensic capacity across regions. Overall, this review underscores the continuing evolution of forensic DNA typing and emphasizes the importance of standardized protocols, interdisciplinary collaboration, and region-specific validation to ensure the reliable and responsible application of DNA evidence in modern forensic science.